Investigation of morphology changes in Karun River and its hazards (Case Study: Bandagir to Khorramshahr) - Amir Saffati; EzatAllah ghanavati; Hamid Alipour Dezdouli Asl (تحقیقات کاربردی علوم جغرافیایی)
Studying the morphology of the rivers and identifying the causes of these changes are widely useful in determining the evolution of rivers and planning the maintenance of the river system. The Karun River, between Bandar-e-Khoramshahr and the constant flow of water in the country, plays an important role in the country's water cycle. Due to the morphological changes of this river that have disrupted the normal functioning of the river, it is necessary to investigate the morphological changes and its causes. In this study, with the aim of investigating these changes with satellite imagery, Landsat images for 1990, 2005 and 2018 were prepared and morphological changes were extracted after required processing. The results show that out of the 36 investigated sections, the width of the river has decreased in 29 sections so that it has narrowed to 450 m around Ahwaz. In order to investigate the causes of changes, the effective parameters in changes such as precipitation, discharge, runoff coefficient, waterway length, permeability coefficient, landform, lithology, land use change, wasteland, slope percentage, drainage density and vegetation density, land Theology and floodplains, To assess the hazards of the area, were used. Floodplain parameter was extracted using ANP_Fuzzy model and landslide and land use parameters were extracted using SVM model. Among the factors affecting these changes that were investigated using logistic regression models and factor analysis were land use changes, vegetation density and sediment yield. These changes have resulted in the destruction of natural habitats along the river, the ability to self-purify water, sudden floods, threatening and damaging human structures, agriculture, and so on.